Summary of the workshop on Climate mitigation policies in developing countries - Gisèle Müller (Fondation pour les études et recherches sur le développement international (FERDI), 2015)
As background preparation for the 21st Conference of the Parties (COP) to the United Nations Framework Convention on Climate Change (UNFCCC) in Paris in December 2015, the FERDI (Fondation pour les Etudes et Recherches sur le Développement International), in collaboration with CERDI (Centre for Studies and Research on International Development) from the University of Auvergne and IDDRI (Institute for Sustainable Development and International Relations), held a one-day workshop on the topic of current and future climate change policies with a special focus on challenges faced by developing countries which will be hardest hit by global warming.
Keywords: 330